2018
DOI: 10.1093/ehjci/jey024
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of myocardial work from pressure–strain loops analysis: an experimental evaluation

Abstract: The non-invasive estimation for LV pressure-strain loop area and the global myocardial work indices obtained from LV-PSL strongly correlates with invasive measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
161
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(166 citation statements)
references
References 21 publications
5
161
0
Order By: Relevance
“…,15,25 In the present study, we show that in patients with severe functional mitral regurgitation, myocardial constructive work is able to detect subtle improvement in LV performance, despite the absence of modification in GLS or LVEF. In a previous study, we demonstrated that a significant reduction in myocardial constructive work is associated with poor LV remodeling after CRT 24.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…,15,25 In the present study, we show that in patients with severe functional mitral regurgitation, myocardial constructive work is able to detect subtle improvement in LV performance, despite the absence of modification in GLS or LVEF. In a previous study, we demonstrated that a significant reduction in myocardial constructive work is associated with poor LV remodeling after CRT 24.…”
supporting
confidence: 53%
“…The area within the PSL is used for the calculation of myocardial work parameters: global constructive work (GCW, work performed during shortening in systole adding negative work during lengthening in isovolumetric relaxation); global wasted work (GWW, negative work performed during lengthening in systole adding work performed during shortening in isovolumetric relaxation); global work index (GWI, constructive work subtracted by wasted work); and global work efficiency (GWE, constructive work divided by the sum of constructive and wasted work) (Figure 1) 15. The software then constructs a non-invasive LV pressure curve adjusted according to the duration of isovolumic and ejection phases defined by valvular timing events at echocardiography.…”
mentioning
confidence: 99%
“…The modern measurement of myocardial work using brachial artery cuff pressure and left ventricular strain analysis is based on the calculation of pressure‐strain loops . The global myocardial work indices obtained by this method correlate strongly with invasive measurements . These results raise the question of the relevance of myocardial work indices in daily practice, and in particular, their usefulness for estimating the severity and predicting the outcome in patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…6 The global myocardial work indices obtained by this method correlate strongly with invasive measurements. 14 Normal values have recently been published and work indices have been measured in patients with heart failure. 7,9,15 This work describes for the first time the relation between classic prognostic parameters and work indices in a heart failure population.…”
Section: Discussionmentioning
confidence: 99%
“…Russel et al recently proposed a method for the non‐invasive estimation of regional and global myocardial work (MW) from pressure‐strain loops (PSLs) analysis . The non‐invasive evaluation of (MW) was validated against the invasive estimation of myocardial performance in patients with CRT, and other cardiac pathologies . PSLs areas were shown to be strongly associated with myocardial oxygen consumption measured at PET, and myocardial constructive work emerged as a predictor of CRT response in heart failure patients undergoing CRT implantation …”
Section: Introductionmentioning
confidence: 99%